Perjuangan Rakyat Rantau Prapat di Kabupaten Labuhanbatu Tahun 1945-1949 - Khoirul Rahma Rambe; Rusdi, Rusdi (Jurnal Pendidikan Tambusai, 2024)
This study examines the People's Struggle of Rantau Prapat in Labuhanbatu Regency in the years 1945-1949. The method used in this research is the historical method with four stages of research methods, namely heuristics, source criticism, interpretation, and histiography. The result of the research is the struggle to maintain independence in Rantau Prapat, which is a collaboration between the TNI guerrilla forces and the Rantau people. The struggle of the Rantau Prapat people in Labuhanbatu cannot be separated from the outbreak of fighting in Medan Area, which resulted in the movement of the enemy to the areas around Asahan-Labuhanbatu. In this struggle, the people of Rantau Prapat supported the movement of the guerrilla army. Various thrilling events that certainly occurred such as the attack on the first Rantau Prapat plantation which occurred on July 22, 1947, and the fighting situation in Rantau Prapat, the fighting situation in Rantau Prapat occurred on December 19, 1948. A thrilling battle that was certainly led by a great command and strong guerrilla forces and of course the people who continued to encourage the guerrilla forces.